Chapter Foreword Reimagining Education Research Practices - from the South to North - Smith, Linda Tuhiwai (Taylor & Francis, 2024)
Sharlene Swartz, Nidhi Singal, Madeleine Arnot, research methods, educational research methods, research methods in education, Global South, southern contexts, decolonization, decolonizing education